ANALISIS PENGARUH KUALITAS WEBSITE TERHADAP KEPUTUSAN PEMBELIAN TIKET PADA FAST BOAT BLUEWATER EXPRESS SERANGAN, BALI - Indrawan, I Gede Fajar; Kusuma Negara, I Made; Agus Wikanatha Sagita, Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
This research aims to find out the website quality of BlueWater Express e-commerce website through several stages, namely: identification of dimensions Usability, Information Quality, and Sevice Interaction Quality. Further reviewed how the influence of Website Quality from e-commerce website BlueWater Express can affect the decision to purchase BlueWater Express fast boat tickets. Data collection techniques using observations, interviews, questionnaires, literature studies, and documentation. Data collection techniques use non-probability sampling with accidental sampling procedure. Analysis techniques using qualitative descriptive analysis and multiple linear regression analysis. The results of this study showed that the Usability dimension (x1) had a positive and significant effect of 0.000 on the purchase decision (y), the Information Quality dimension (x2) had a positive and significant effect of 0.000 on the purchase decision (y), the dimension of Sevice Interaction Quality (x3) has a positive and significant effect of 0.000 on purchasing decisions (y), and the three dimensions of Usability (x1), Information Quality (x2), and Sevice Interaction Quality (x3) simultaneously positively affect purchasing decisions (y). From the Website Quality, information quality is the biggest factor influencing the decision of tourists to buy BlueWater Express fast boat tickets directly on the BlueWater Express e-commerce website itself. This is because the information presented on the BlueWater Express website is always up to date and can be accounted for.